2019
DOI: 10.1186/s40965-019-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

The LandInfra standard and its role in solving the BIM-GIS quagmire

Abstract: LandInfra is a relatively new open standard for modelling and representing land and infrastructure features. As it overlaps with other open standards in BIM (IFC) and 3D GIS (CityGML), it has been recognised as a potential candidate to bridge the gap between the two domains. However, the knowledge of this standard in both communities is low, and there are still no publications which fully explore LandInfra and its possibilities for integrated BIM-GIS applications. In this paper, we review the LandInfra concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…LandInfra and CityGML have significant similarities and differences, which we have discussed in detail in Kumar et al [30]. After comparing the two standards and analysing the individual correspondences of the classes, attributes and other concepts in the data model of LandInfra to their equivalent ones in CityGML, we found that they fit into five different categories as mentioned below.…”
Section: Mapping Between Landinfra and Citygmlmentioning
confidence: 73%
“…LandInfra and CityGML have significant similarities and differences, which we have discussed in detail in Kumar et al [30]. After comparing the two standards and analysing the individual correspondences of the classes, attributes and other concepts in the data model of LandInfra to their equivalent ones in CityGML, we found that they fit into five different categories as mentioned below.…”
Section: Mapping Between Landinfra and Citygmlmentioning
confidence: 73%
“…The most prominent open standards in the geoinformation domain are: the OGC standard CityGML [37] for storage and exchange of 3D city models, the international IFC standard [25] for BIM models, the OGC standard LandInfra [38] and its GML-based encoding, InfraGML modelling and representing land and infrastructure features. There are several studies that investigate the interoperability between those standards, as well as a recent research by Kumar et al [39] that analyses the differences and similarities between those three standards, with regards to certain criteria as geometry, topology, semantics, encodings, etc. With respect to the legal and administrative information, the most dominant standards are the ISO standard LADM [4] and e-Plan, mostly used in Australia, New Zealand and Singapore.…”
Section: Importance Of Standardsmentioning
confidence: 99%
“…Therefore, the integration of BIM and GIS has been considered a promising topic for cross-domain knowledge exchange [8][9][10]. Integration has become especially relevant with the extensive use of BIM for infrastructure, as infrastructure projects extend over large geographic areas and relate more to other features from the natural and built environment than what has typically been handled in BIM [11].…”
Section: Building Information Modelling (Bim) and Geographic Informatmentioning
confidence: 99%
“…Niestroj et al [36] discussed information models for road asset information exchange and noted that InfraGML might be easier to implement than IFC as GIS applications widely support the GML format. Kavisha et al [11] discussed the LandInfra/InfraGML standards and the IFC Infrastructure extensions and noted that LandInfra/InfraGML could help bridge the gap between BIM and GIS.…”
Section: Integration Of Bim and Gismentioning
confidence: 99%